Filtering Communication Media as an Antidote to the Spread of Hoax News: Study of Takhrij and Syarah Hadith - Salsabila, Ghina; Latif, Muhammad Farhan Fauzan (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study is to discuss how communication media filter the spread of hoax news. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the spread of hoax news in communication media on hadith narrated by Ibnu Majah No. 30. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi fulfills the qualifications of maqbul ma'mul bih for Islamic practice. This study concludes that the hadith narrated by Ibn Majah No. 30 relevant is used as motivation, creativity, innovation, and development of the field of communication in filtering news or information.